Coordination of carbon assimilation, allocation, and utilization for systemic improvement of cereal yield - Liang, Xiao-Gui; Gao, Zhen; Fu, Xiao-Xiang; Chen, Xian-Min; Shen, Si; Zhou, Shun-Li (Frontiers in Plant Science, 2023)
The growth of yield outputs is dwindling after the first green revolution, which cannot meet the demand of the projected population increase by mid-century, especially with the constant threat from extreme climates. Cereal yield requires carbon (C) assimilation in the source for subsequent allocation to, and utilization in the sink. Whether the source or the sink limits yield improvement, a crucial question for strategic orientation in future breeding and cultivation, however, is still under debate. To narrow the knowledge gap and capture the progress, here we focus on maize, rice, and wheat, by briefly reviewing recent advances for yield improvement by modulation of i) leaf photosynthesis; ii) primary C allocation, phloem loading, and unloading; iii) C utilization and grain storage; and iv) systemic sugar signals (e.g., trehalose 6-phosphate), we highlight those strategies of optimizing C allocation and utilization to coordinate the source-sink relationships and promote yields. Finally, based on the understanding of these physiological mechanisms, we envisage a future scenery of "smart crop" consisting of flexible coordination of plant C economy, with the goal of yield improvement and resilience in the field population of cereals crops.